Poster Presentations 2017
DOI: 10.1136/annrheumdis-2017-eular.2729
|View full text |Cite
|
Sign up to set email alerts
|

SAT0366 Smoking behaviour and the progression of organ manifestations in systemic sclerosis: a longitudinal european scleroderma trials and research group study

Abstract: BackgroundSystemic sclerosis (SSc) is a rare, multisystem autoimmune disorder. It is characterised by generalized microangiopathy, in which hypoxia and oxidative stress have been implicated in its pathogenesis. Tobacco inhalation increases free radicals and strongly promotes vascular damage. So far, data available with regards to a role of tobacco exposure with SSc severity and progression are scarce.ObjectivesWe aimed to assess the effects of smoking on the speed of worsening of organ manifestations, namely l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In this study, however, in comparison with others in the literature, there was a higher proportion of non-white patients, which could indicate an association between differing genetic, environmental, and digital vascular insults. Similarly, in a recent study by Jaeger et al [ 14 ] in 2017, smoking was not associated with DUs in the European Scleroderma Trials and Research Group (EUSTAR) cohort of 3023 patients.…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…In this study, however, in comparison with others in the literature, there was a higher proportion of non-white patients, which could indicate an association between differing genetic, environmental, and digital vascular insults. Similarly, in a recent study by Jaeger et al [ 14 ] in 2017, smoking was not associated with DUs in the European Scleroderma Trials and Research Group (EUSTAR) cohort of 3023 patients.…”
Section: Introductionmentioning
confidence: 71%
“…[ 9 , 10 ] Several studies have also looked at the cause–effect relationship between smoking and vascular outcomes in SSc with conflicting results. [ 11 , 12 , 13 , 14 ] Harrison et al [ 11 ] demonstrated in a cross-sectional study of 101 patients with SSc in Manchester, United Kingdom, that current smokers were 3–4 times more likely than never smokers to develop digital vascular disease and require treatment (IV Prostanoid, debridement, or amputation). However, interestingly, in this study, past smokers were not at increased risk in comparison with never smokers.…”
Section: Introductionmentioning
confidence: 99%